PERAN MEDIA AUDIO VISUAL DALAM MENINGKATKAN KETERLIBATAN ANAK -ANAK SEKAMI DALAMKEGIATAN IMAN DI PAROKI ST. IGNASIUS WAIBALUN - Maria M. Odjan; Maria F. L. Kota; Ursulin Fako (Adiba Aisha Amira, 2026)
This study aims to determine the role of audio-visual media in increasing the involvement of SEKAMI children in faith activities at St. Ignatius Waibalun Parish. The background of this study is based on the low participation and active involvement of children in SEKAMI activities, which tend to be monotonous and less attractive. Therefore, innovation in faith formation methods is needed through the use of more interactive and engaging audio-visual media. This study employed a Community Service (PKM) approach with participatory, educational, and applicative models. The activities were carried out through the stages of preparation, implementation, mentoring, and evaluation. The audio-visual media used included spiritual videos, Biblical animation films, and religious songs in faith formation activities. The results showed that the use of audio-visual media was able to increase children’s enthusiasm, participation, and active involvement in SEKAMI faith activities. In addition, children were able to understand the material more easily through attractive visual and audio presentations. Therefore, audio-visual media has a significant role in supporting the faith formation process of SEKAMI children and can serve as a creative and effective method for children’s faith mentors.